Water chemistry of nuclear reactor systems 3 : proceedings of an international conference organised by the British Nuclear Energy Society and co-sponsored by the Institution of Chemical Engineers and the Royal Society of Chemistry, Bournemouth, 17-21 October, 1983. Vol. 1 (British Nuclear Energy Society, 1983)
Proceedings of third international conference held in Bournemouth on 17-21 October 1983.